(untitled) (Revista História & Perspectivas, 2009)
Neste trabalho procuro mapear os espaços ocupados por imigrantes e trabalhadores nacionais pobres ligados ao abastecimento alimentício da cidade de São Paulo, entre as últimas décadas do século XIX e as primeiras décadas do XX, analisando onde viviam e como produziam e comercializavam alimentos. Ao mesmo tempo, acompanha parte das remodelações de algumas áreas da cidade e o progressivo afastamento das áreas de cultivo. PALAVRAS-CHAVE: Trabalhadores. Cidade. Comércio. São Paulo. História. ABSTRACT In this paper, I aim to identify the spaces occupied by immigrants and Brazilian poor workers into the food supply chain in São Paulo city, between last decades of XIX and first decades of XX, analyzing where they used to live and how they produced and comercialized food. At the same time, this paper follows part of the reestructuration process of some areas in the city and the progressive changes which moved cultivation fields apart. KEYWORDS: street workers. City. Commerce. São Paulo. History.